2021
DOI: 10.1212/wnl.0000000000011051
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Trajectories in Type 2 and 3 Spinal Muscular Atrophy in the iSMAC Cohort Study

Abstract: Objective.To describe the respiratory trajectories and their correlation with motor function in an international paediatric cohort of patients with type 2 and non-ambulant type 3 spinal muscular atrophy (SMA).Methods.Eight-year retrospective observational study of patients in the iSMAc natural history study. We retrieved anthropometrics, forced vital capacity (FVC) absolute, FVC% predicted (FVC%P.), Non-Invasive ventilation (NIV) requirement. Hammersmith functional motor scale (HFMS) and Revised performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 38 publications
12
41
2
4
Order By: Relevance
“…This respiratory function decline is in line with previous studies, but those studies included data mainly from type II patients 5,19 . Type II patients are considered more severely affected and yet their RULM scores are comparable with type III patients who have also lost ambulation 11,20 . The average FVC% decrease was a statistically significant 17% at 24 months.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This respiratory function decline is in line with previous studies, but those studies included data mainly from type II patients 5,19 . Type II patients are considered more severely affected and yet their RULM scores are comparable with type III patients who have also lost ambulation 11,20 . The average FVC% decrease was a statistically significant 17% at 24 months.…”
Section: Discussionsupporting
confidence: 87%
“…These inconsistent descriptions are likely to complicate evaluation of treatment‐related clinical data and may in part be due to the limited scope of motor performance measures used in this group. Studies have suggested that SMA III individuals are less likely to develop scoliosis and have little respiratory muscle weakness compared with type II patients, yet newer evidence has shown respiratory complications in type III patients 1,6,11 . Nonambulant pediatric SMA III patients commonly develop contractures and scoliosis, which requires spinal fusion when the deformity is sufficiently severe 6 …”
Section: Introductionmentioning
confidence: 99%
“…The convergent validity of FVC% has been previously assessed in a large cohort of SMA patients, mostly children. 39 This study confirms moderate correlations of FVC% with functional scales, albeit its discriminating ability and responsiveness was overall low. However, it may still be useful in non-sitters, in whom its responsiveness is higher and respiratory endpoints are particularly clinically meaningful.…”
Section: Fvc%supporting
confidence: 75%
“…The convergent validity of FVC% has been previously assessed in a large cohort of SMA patients, mostly children. 39 This study confirms moderate correlations of FVC% with functional scales, albeit its discriminating ability and responsiveness was overall All rights reserved. No reuse allowed without permission.…”
Section: Fvc%supporting
confidence: 75%
“…Similar to DMD, in spinal muscular atrophy (SMA) FVC is a viable parameter for longitudinal monitoring of progression in respiratory muscle weakness 6 . Baseline absolute FVC and FVC% predicted is lower in patients with SMA type 2 compared with patients with SMA type 3 and these decline between the ages of 5 and 13 years and more slowly thereafter 6–8 . In one of the largest and most comprehensive cohort studies of treatment—naïve patients with SMA, Wijngaarde et al 9 showed significant differences in baseline VC% predicted showed that the average rate of change in VC% predicted declined by 1.57% per year in type 2a, 1.65% in type 2b, and 1.06% in type 3a.…”
Section: Volumementioning
confidence: 99%